Pemberdayaan Ekonomi Masyarakat Mandiri melalui Literasi Pemasaran Digital di Era Global - Leni Winarni; Arofah Minasari; Ferdian Ahya Al Putra (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2023)
The rapid revolution of information technology makes some people not ready to adapt to societal changes; therefore, they cannot utilize it optimally. Instead of having a positive impact, on the contrary, this technological progress is considered to have a negative effect. In this context, it needs to be addressed in two ways: firstly, increasing digital literacy can provide an understanding of the use of platforms, especially on the Internet and social media; secondly, utilizing social media to improve the standard of living for the community. Through the community service program in the villages of Tambakboyo, Tawangsari, Sukoharjo, we are trying to provide literacy education regarding digital marketing strategies to the community. We conducted the workshop in the village because most people work in textile companies, which means they can develop their ability in sewing and creativity with the waste of patchwork to increase their income, especially women. Depart from our observation in the field, we found that not many mothers became entrepreneurs using patchwork, even though almost all of them had sewing machines. Besides that, many do not yet use social media for entrepreneurship for various reasons. However, we believe that small efforts to pioneer UMKM (Usaha Mikro, Kecil, dan Menengah (Micro Small and Medium Enterprises)) digital marketing are promising in the future since it will expand the UMKM network globally as a part of diplomacy economy.